2007
DOI: 10.1073/pnas.0610337104
|View full text |Cite
|
Sign up to set email alerts
|

Blocking S -adenosylmethionine synthesis in yeast allows selenomethionine incorporation and multiwavelength anomalous dispersion phasing

Abstract: Saccharomyces cerevisiae is an ideal host from which to obtain high levels of posttranslationally modified eukaryotic proteins for x-ray crystallography. However, extensive replacement of methionine by selenomethionine for anomalous dispersion phasing has proven intractable in yeast. We report a general method to incorporate selenomethionine into proteins expressed in yeast based on manipulation of the appropriate metabolic pathways. sam1 ؊ sam2 ؊ mutants, in which the conversion of methionine to S-adenosylmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 51 publications
5
65
0
Order By: Relevance
“…As found for A. nidulans, yeast Sam1 also recruits proteins required for morphogenesis like the aconitase Aco1 or a-tubulin Tub1 (Gavin et al, 2006). In addition, the recruitment of the cobalamin-independent methionine synthetase Met6 (Malkowski et al, 2007) and the heat shock protein Ssa1 (Gong et al, 2009) seem to be conserved. Heat shock proteins are methylated in response to stress (Chiang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As found for A. nidulans, yeast Sam1 also recruits proteins required for morphogenesis like the aconitase Aco1 or a-tubulin Tub1 (Gavin et al, 2006). In addition, the recruitment of the cobalamin-independent methionine synthetase Met6 (Malkowski et al, 2007) and the heat shock protein Ssa1 (Gong et al, 2009) seem to be conserved. Heat shock proteins are methylated in response to stress (Chiang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…4C, equivalent partial resistance is seen for the sam1⌬ or sam2⌬ single-deletion strains, and additive resistance was seen for the sam1⌬ sam2⌬ strain equivalent to the cys3⌬ strain up to 0.15 mM. Malkowski et al (9) demonstrated that deletion of the SAM1 gene resulted in greater resistance than deletion of the SAM2 gene. To determine the possible reasons for this difference, sam1⌬ and sam2⌬ single-mutant strains as well as a sam1⌬ sam2⌬ double-mutant strain in the BY4742 (MAT␣ MET15) were analyzed for SeMet resistance.…”
Section: Semet Incorporation Into Proteins In a Cys3⌬ Null Strain By mentioning
confidence: 99%
“…Thus, the single cys3⌬ deletion shows equivalent resistance to SeMet as the sam1⌬ sam2⌬ strain. Analysis of SeMet occupancy in a protein purified from the sam1⌬ sam2⌬ strain showed 83% occupancy in the presence of 0.125 mM SeMet and 95% occupancy in 0.5 mM SeMet (9). To compare the results for an expressed protein in the cys3⌬ and sam1⌬ sam2⌬ strain, a plasmid expressing 6ϫHis tagged S. cerevisiae eEF1B␣ was transformed into each strain.…”
Section: Semet Incorporation Into Proteins In a Cys3⌬ Null Strain By mentioning
confidence: 99%
See 2 more Smart Citations